The Myth in the Arabian Sources - Mohammad Kazem , Lect. Dr.Thikraa (Basra studies journal, 2022)
The myth in historical novels has occupied great importance by historians and researchers, in order to give a real view of many historical tales that are often accused of skepticism and the emplacement. In order to raise such beliefs prevailing among some who believe that the history of Arabs before Islam was considered an era of chaos and cultural confusion, while the history of the Arabs before Islam became the basic rule in the study of Arab and Islamic history The sources of pre-Islamic Arab history and Islamic history have had many narrations, and books were filled with many narrations that included talisman, magic and superstition –whose main source was the books of the Torah and the narrations of the Jewish rabbis, which has the greatest impact in distorting the origins of Islamic history In order to understand the contents of these myths, superstition evidence was extracted, most notably to explore the mysteries of these evidence, clarify their facts, and prove their credibility or not. It is difficult to classify the myths that have been extracted so that the each myth fits with its peers and counterparts, and the researcher have endeavored as much as possible to classify these myths and include the similar ones to each other as the matter for this study settled in the end on the following matters. The study revealed the exaggerations of some Arab and Islamic sources about the interpretation of historical evens whose contents are impossible for the mind to accept.